A Single Number Index to Assess Selected Acoustic Parameters in Churches with Redundant Information - KOSAŁA, Krzysztof (Archives of Acoustics, 2011)
The paper presents an innovative approach for the index assessment of the acous-tic properties of churches. A new formula for an approximate single number indexto assess selected acoustic parameters of church interiors, such as reverberation time(RT), speech intelligibility index (RASTI) and music clarity index (C80), is presentedin the paper. The formula is created by means of the Singular Value Decomposition(SVD) method. An innovative approach for calculating the weights of partial in-dices is shown by solving the problem of redundant information, i.e., the system ofoverdetermined linear equations, using a computed pseudoinverse matrix. The newprocedures for calculating the values of three partial indices and the single numberindex to assess selected acoustic parameters are presented. The proposed methodwas verified by measurements in several selected churches.